2015
DOI: 10.1111/hae.12665
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with central venous access device in children with haemophilia: a nationwide multicentre study in Finland

Abstract: Children with haemophilia require venous access for regular infusion of coagulation factors. A central venous access device (CVAD) ensures long-term access but associates with infectious and non-infectious complications with proposed risk factors of young age at initial CVAD implantation and presence of an inhibitor. Our aim was to evaluate the incidence and risk factors for complications associated with CVAD usage in a retrospective nationwide multicentre study in five Finnish Paediatric Haemophilia Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
2
10
1
2
Order By: Relevance
“…Risk factors for infection include young age at time of placement and use of external CVADs . Although some studies report younger age at placement as a risk factor for infections, in our study, frequency of infections was higher among the older children.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Risk factors for infection include young age at time of placement and use of external CVADs . Although some studies report younger age at placement as a risk factor for infections, in our study, frequency of infections was higher among the older children.…”
Section: Discussioncontrasting
confidence: 59%
“…The benchmark estimate for the incidence of infection in this population is based on pooled data from a 2004 meta‐analysis that reported 0.66 catheter‐associated infections per 1000 CVAD days, with a pooled time to the first infection of 295 days (95% CI: 181‐479 days) . A more recent study from Finland of 58 paediatric haemophilia patients with CVADs found a very low bloodstream infection rate (0.12/1000 CVAD days) nationwide . A 1992‐2009 study from Australia reported the overall incidence of confirmed CVAD‐related bloodstream infection was 0.42 per 1000 CVAD days (95% CI: 0.31‐0.58/1000) and that 29 (51.8%) of 56 patients experienced CVAD‐related infections .…”
Section: Discussionmentioning
confidence: 99%
“…Local infection was defined as catheter insertion local exit-site infection. Catheter-related thrombosis was diagnosed by ultrasound with clinical symptoms or signs of venous thrombosis 15. Mechanical phlebitis was defined as at least one sign or symptom of vein irritation confined to the CVC insertion site 16.…”
Section: Methodsmentioning
confidence: 99%
“…Так, в нескольких ста-тьях проанализирован опыт применения ИВПС у детей с орфанными заболеваниями [25][26][27]; в 2 -у детей с гемофилиями [28,29]; в 3 -с ВИЧ-инфекциями [30][31][32], однако работы последней группы описыва-ют опыт применения преимущественно у взрослых пациентов, и по этой причине в литературный обзор включены не были. Обращает на себя внимание тот факт, что частота инфекционных осложнений у боль-ных ВИЧ была выше по сравнению с пациентами, кото-рым ИВПС устанавливали для лечения онкологических заболеваний [27].…”
Section: особенности анестезиологического пособияunclassified
“…Интересно, что анестезия выполнялась с помо-щью внутривенного введения кетамина и мидазолама в сочетании с масочной анестезией закисью азота. Такой вариант анестезиологического пособия, возможно, объ-ясняется тем, что статья датирована 2009 г., поскольку в настоящее время оптимальным считается применение масочной анестезии cевофлураном [29].…”
Section: особенности анестезиологического пособияunclassified